2018
DOI: 10.1126/sciadv.aao7265
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectrochemical CO production: Implications for the autotrophic origin of life

Abstract: Efficient CO production realizing Wächtershäuser’s scenario was demonstrated in simulated early ocean hydrotherm systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 69 publications
(102 reference statements)
4
99
0
Order By: Relevance
“…Actually, Ni‐doped iron‐sulfide electrodes promote the reduction of carbon dioxides in the presence of proton gradient . Also, cadmium sulfide can electrochemically reduce carbon dioxides to carbon monoxide at the faraday efficiency of ∼40 % . Carbon monoxide is highly reactive, and various organic compounds including amino acids are synthesized from carbon monoxide using sulfide catalysts .…”
Section: Spin‐off Studies Based On Deep‐sea Electricity Generationmentioning
confidence: 99%
“…Actually, Ni‐doped iron‐sulfide electrodes promote the reduction of carbon dioxides in the presence of proton gradient . Also, cadmium sulfide can electrochemically reduce carbon dioxides to carbon monoxide at the faraday efficiency of ∼40 % . Carbon monoxide is highly reactive, and various organic compounds including amino acids are synthesized from carbon monoxide using sulfide catalysts .…”
Section: Spin‐off Studies Based On Deep‐sea Electricity Generationmentioning
confidence: 99%
“…[10] This driving force can be obtained if we also consider the elevated temperature of the hydrothermal fluid (~500 K), as the H + /H 2 redox potential is shifted even more negatively to À 780 mV ( Figure 4B, red line). [10,18] As to how this driving force is used to reduce CO 2 , it is worth noting that the thermodynamics become more favorable upon transferring more electrons (Table 1). [10,18] As to how this driving force is used to reduce CO 2 , it is worth noting that the thermodynamics become more favorable upon transferring more electrons (Table 1).…”
Section: Use Of 3d Structures For Driving Co 2 Reductionmentioning
confidence: 99%
“…[18,23,24] The reactivity trends across different materials have been rationalized largely based on the d-band theory and the Sabatier principle. Up to this date, there have been many studies in the field of electrocatalysis, where the catalyst has been shown to markedly influence the selectivity and activity (overpotentials) of this reaction.…”
Section: Usage Of Sequential Proton-electron Transfer (Spet) To Regulmentioning
confidence: 99%
See 2 more Smart Citations